(untitled) (Research, Society and Development, 2021)
This article aims to analyze the perception of workers with noise-induced hearing loss (NIHL) in relation to their working conditions and their trajectory through the health care network. This is an exploratory study with a qualitative approach, based on notifications by NIHL carried out by the main auditory reference in secondary care in the period from 2016 to 2018. The results show the perceptions of workers with NIHL and their effects on noise exposure, chemical and ergonomic risks, painful working conditions, use of protective equipment, job satisfaction, demand for health services. The attendance at the health service network will allow the identification of the probable hearing problem, the perception of the reception received by the basic health unit and the consequences of the case. It is concluded that the basic health unit needs adjustments in order to improve its function in the network, regarding the return and monitoring of the working user after the diagnosis of NIHL, as well as review of the monitoring and evaluation in the guidelines (flow and counterflow) and readjust the worker health management process.